Myosin Light Chain 9/12 Regulates the Pathogenesis of Inflammatory Bowel Disease - Yokoyama, Masaya; Kimura, Motoko Y.; Ito, Toshihiro; Hayashizaki, Koji; Endo, Yukihiro; Wang, Yangsong; Yagi, Ryoji; Nakagawa, Tomoo; Kato, Naoya; Matsubara, Hisahiro; Nakayama, Toshinori (Frontiers in Immunology, 2021)
The numbers of patients with inflammatory bowel disease (IBD), such as ulcerative colitis (UC) and Crohn’s disease (CD), have been increasing over time, worldwide; however, the pathogenesis of IBD is multifactorial and has not been fully understood. Myosin light chain 9 and 12a and 12b (Myl9/12) are known as ligands of the CD69 molecule. They create “Myl9 nets” that are often detected in inflamed site, which play a crucial role in regulating the recruitment and retention of CD69-expressing effector cells in inflamed tissues. We demonstrated the strong expression of Myl9/12 in the inflamed gut of IBD patients and mice with DSS-induced colitis. The administration of anti-Myl9/12 Ab to mice with DSS-induced colitis ameliorated the inflammation and prolonged their survival. The plasma Myl9 levels in the patients with active UC and CD were significantly higher than those in patients with disease remission, and may depict the disease severity of IBD patients, especially those with UC. Thus, our results indicate that Myl9/12 are involved in the pathogenesis of IBD, and are likely to be a new therapeutic target for patients suffering from IBD.